Dopaminergic and GABA‐ergic markers of impulsivity in rats: evidence for anatomical localisation in ventral striatum and prefrontal cortex. Issue 9 (1st February 2013) - Jupp, Bianca; Caprioli, Daniele; Saigal, Niel; Reverte, Ingrid; Shrestha, Saurav; Cumming, Paul; Everitt, Barry J.; Robbins, Trevor W.; Dalley, Jeffrey W.
Abstract Accumulating evidence indicates that impulsivity, in its multiple forms, involves cortical and subcortical mechanisms and abnormal dopamine (DA) transmission. Although decreased DA D2/D3 receptor availability in the nucleus accumbens (NAcb) predicts trait‐like impulsivity in rats it is unclear whether this neurochemical marker extends to both the NAcb core (NAcbC) and shell (NAcbS) and whether markers for other neurotransmitter systems implicated in impulsivity such as serotonin (5‐HT), endogenous opioids and γ‐amino‐butyric acid (GABA) are likewise altered in impulsive rats. We therefore used autoradiography to investigate DA transporter (DAT), 5‐HT transporter (5‐HTT) and D1, D2/D3, μ‐opioid and GABA(A) receptor binding in selected regions of the prefrontal cortex and striatum in rats expressing low and high impulsive behaviour on the five‐choice serial reaction‐time task. High‐impulsive (HI) rats exhibited significantly lower binding for DAT and D2/D3 receptors in the NAcbS and for D1 receptors in the NAcbC compared with low‐impulsive (LI) rats. HI rats also showed significantly lower GABA(A) receptor binding in the anterior cingulate cortex. For all regions where receptor binding was altered in HI rats, binding was inversely correlated with impulsive responding on task. There were no significant differences in binding for 5‐HTT or μ‐opioid receptors in any of the regions investigated. These results indicate that altered D2/D3 receptor binding is localised to the NAcbS of trait‐like impulsive rats and is accompanied by reduced binding for DAT. Alterations in binding for D1 receptors in the NAcbC and GABA(A) receptors in the anterior cingulate cortex demonstrate additional markers and putative mechanisms underlying the expression of behavioural impulsivity.